MOOCs Concept and Design using cloud-based Tools: Spanish MOOCs Learning Experiences - Rizzardini, R.; Morales, M.; Gϋtl, Christian; Chang, Vanessa (MIT, 2013)
New forms of education and media technologies as well as the availability of affordable devices, free services and open content have strongly influenced modern learning settings. The advent of open courses have demolished organizational restrictions and dramatically increased the number of participating students. MOOCs have become increasingly popular. This situation has motivated research and development of MOOCs making use of cloud-based learning tools and online tools as well as learning support specifically for Spanish speaking learners. Experimentation and findings from two MOOCs experiences have shown promising results in terms of motivational, emotional and educational aspects. On the negative side there is still a high dropout rate and challenges with interaction and collaboration among peers.